Development of Android-Based BIPAS Learning Media in MI/SD - Setria Rizal; Silviyanti Silviyanti; Muhammad Syabrina (PGMI IAIN Lhokseumawe, 2023)
Learning media is something that has an important role in the learning process, with the presence of learning media material that was previously difficult for students to understand or even abstract will become concrete with the help of learning media. The purpose of this study was to produce android-based BIPAS learning media on the theme